1982
DOI: 10.1007/bf00239377
|View full text |Cite
|
Sign up to set email alerts
|

Kinaesthetic role of muscle afferents in man, studied by tendon vibration and microneurography

Abstract: The characteristics of vibration-induced illusory joint movements were studied in healthy human subjects. Unseen by the subject, constant frequency vibration trains applied to the distal tendon of the Triceps or Biceps induced an almost constant velocity illusory movement of the elbow whose direction corresponded to that of a joint rotation stretching the vibrated muscle. Vibration trains of the same duration and frequency applied alternatively to the Biceps and Triceps evoked alternating flexion-extension ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
493
3
12

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 844 publications
(528 citation statements)
references
References 28 publications
20
493
3
12
Order By: Relevance
“…We think this choice is justifiable for two reasons. First, results in microneurography studies have demonstrated a major role of muscle spindles in proprioception (Cordo et al 1995;Goodwin et al 1972a;Roll and Vedel 1982) and muscle spindles are the primary sensory resource of information for maintaining balance during upright stance . Second, anesthetizing joint receptors only results in an increased positioning error in passive repositioning (Konradsen et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think this choice is justifiable for two reasons. First, results in microneurography studies have demonstrated a major role of muscle spindles in proprioception (Cordo et al 1995;Goodwin et al 1972a;Roll and Vedel 1982) and muscle spindles are the primary sensory resource of information for maintaining balance during upright stance . Second, anesthetizing joint receptors only results in an increased positioning error in passive repositioning (Konradsen et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle spindles play a major role in proprioception (Cordo et al 1995;Goodwin et al 1972a;Roll and Vedel 1982). In studies on the role of proprioception in standing, vibration is used to analyze the relative contribution of a peripheral proprioceptive signal to the total motor output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local muscle vibration was used to investigate the role of proprioception in postural control. Muscle vibration (60 Hz, 0.5 mm) is a powerful stimulus of muscle spindle Ia afferents, evoking an illusion of muscle lengthening (Cordo et al, 2005;Roll and Vedel, 1982). When the central nervous system uses proprioceptive signals of the vibrated muscles for postural control, this causes a directional corrective center of pressure displacement.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…Tendon vibration offers a means of achieving this end, since it is known to specifically activate muscular proprioception. Indeed, most primary endings respond in a one-to-one manner to a low amplitude vibratory stimulus for frequencies between 1 and 100 Hz (Roll & Vedel, 1982). Such responses of Ia muscle spindle afferents are well known to evoke illusory sensation of movement (Goodwin, McCloskey, & Matthews, 1972).…”
mentioning
confidence: 99%